ANALISIS PENINGKATAN KUALITAS PEMOTONGAN AYAM DENGAN MENGGUNAKAN METODE SIX SIGMA DI PT.GEMILANG INTI SUKSES - Sukron, Ahmad; Sumarsono; Rijanto, Tri (Universitas Hasyim Asy'ari, 2019)
Quality improvement activities can help companies maintain and improve the quality of their products bymaking improvements to the level of being broken product to zero damage. PT. Gemilang Inti Sukses is aProfit-oriented Chicken Porong Home Industry engaged in the agribusiness sector, in the process of cuttingchickens there are several obstacles that can affect the level of quality of chicken slaughtered products,Therefore this study aims to determine the quality problems of chicken slaughter and increase the resultsproduct quality at PT. Gemilang Inti Sukses. The method that will be used in this research is the Six Sigmamethod on the DMAIC (Define, Measure, Analyze, Improve, Control) concept. The results showed that ofthe 20 days sample that was 6,540 tails, it was found that the number of slaughtered chickens was 2,230chickens with the details of bruised chicken heads, broken chicken wings, bruised chicken body parts, lessclean feather extraction, and internal taking. not clean enough. While the company's performancemeasurement is at Sigma 3.85 level with a 9.292 DMPO value, which means that in 1 million pieces ofchicken there are 9,292 chickens that are deformed. From the Pareto diagram, it is known that 80% of thedefects are broken chicken wings and bruised chicken parts. Then from the cause and effect diagram it isknown that human resource factors are the main cause of broken chicken wing flaws and bruised chickenbody parts, therefore from the results of this study the company needs to improve quality with morediscipline towards human resource operational standards and conduct supervision and evaluation ofemployee performance. Keywords: Pareto, Quality Improvement, Cause and Effect, Six Sigma-DMAIC.